2008
DOI: 10.1007/s10695-008-9284-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heavy metals on embryonic development of fish (a review)

Abstract: Early developmental stages of fish are particularly sensitive to water pollution. Heavy metals may affect various developmental processes during the embryonic period, which results in a reduction of offspring quantity and quality. Waterborne metals may accumulate in the gonads of spawners and adversely affect gamete production and viability, or exert direct toxic influence upon developing embryos. The egg shell does not fully protect the embryo against metal penetration, particularly during the swelling phase;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
215
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(236 citation statements)
references
References 72 publications
12
215
0
9
Order By: Relevance
“…One possible explanation to these findings is that an increase in the water temperature during summer increases heavy metals uptake in the fishes as compared to the winter season. Ahmed et al, (2013) supported this claim by stating that seasonal variations with regards to the concentration of heavy metals bio-accumulated in fish species follow a trend whereby the highest levels of heavy metals are accumulated during summer while the lowest values are accumulated during winter due to a rise in temperature which favours the uptake of certain heavy metals.The higher water temperature during the summer season as opposed to the lower temperatures during winter, favours a rise in the accumulation uptake and binding of metals probably due to higher metabolic rate in the fishes as proposed by Jezierska et al, (2009). Obasohan & Eguavoen (2008) also suggested that the rate of pollutant accumulation is favoured during high temperatures as the blood's oxygen affinity is decreased.…”
Section: Inter-species Comparison Within Elementsmentioning
confidence: 94%
See 1 more Smart Citation
“…One possible explanation to these findings is that an increase in the water temperature during summer increases heavy metals uptake in the fishes as compared to the winter season. Ahmed et al, (2013) supported this claim by stating that seasonal variations with regards to the concentration of heavy metals bio-accumulated in fish species follow a trend whereby the highest levels of heavy metals are accumulated during summer while the lowest values are accumulated during winter due to a rise in temperature which favours the uptake of certain heavy metals.The higher water temperature during the summer season as opposed to the lower temperatures during winter, favours a rise in the accumulation uptake and binding of metals probably due to higher metabolic rate in the fishes as proposed by Jezierska et al, (2009). Obasohan & Eguavoen (2008) also suggested that the rate of pollutant accumulation is favoured during high temperatures as the blood's oxygen affinity is decreased.…”
Section: Inter-species Comparison Within Elementsmentioning
confidence: 94%
“…Fishes caught in winter and summer may therefore come from different marine environments and be subjected to different conditions. Jezierska et al (2009) suggested that accumulation is dependent on metal concentration, exposure time, route of metal uptake and environmental conditions such as water temperature, pH, salinity and feeding habits. The fishes caught during both seasons may belong to different schools of fish, come from different marine environments and have distinctive conditions proposed by Jezierska et al,(2009) which would explain the differences in accumulation patterns.…”
Section: Inter-species Comparison Within Elementsmentioning
confidence: 99%
“…Larval normality was analyzed under a stereomicroscope (10×) by evaluating 200 larvae from each experimental unit. Normal larvae were considered as those that showed no morphological alterations in the backbone, yolk sac, or head (FRAYSSE et al, 2006;JEZIERSKA et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…It is well known that aquatic organisms are particularly sensitive to free metals, [27] and exposure at sub-lethal concentrations can affect several processes, including development, [28] movement, [29,30] hatch rate [31][32][33] and ion balance. [34] A major concern associated with metal-based NMs is the dissolution and release of ionic species in aquatic matrices.…”
Section: Dissolution Of Nmsmentioning
confidence: 99%